Pseudomyogenic haemangioendothelioma: a case report and overview of a potential diagnostic pitfall. Issue 1 (January 2022) - De Noon, Solange; Amary, Fernanda
Abstract: Pseudomyogenic haemangioendothelioma (PHE) is a rare vascular tumour which can arise in skin, soft tissue and bone, posing a diagnostic challenge due to its similar histological appearances to several soft tissue and skin neoplasms. We report an unusual case of PHE with aggressive behaviour and provide an overview of this unique entity, discussing important differential diagnoses and highlighting key histological, immunohistochemical and genetic features which aid in its accurate diagnosis.